Réponses

2014-10-22T10:42:30+02:00
Salut,
4x-2+x(x-1)=x²+1
4x-2+x(x-1)-x²-1=0
4x-x+x²-x²-2-1=0
3x=3
x=1
Donc S={1}

(x-2)²+(x-2)(2x+3)=0
(x-2)((x-2)+(2x+3))=0
(x-2)(3x+1)=0
or, un produit est nul si au moins un des facteurs est nul
si x-2=0; x=2
si 3x+1=0; x=-1/3
Donc S={-1/3,2}

(2x-4)²-(x+1)²=0
(2x-4-x-1)(2x-4+x+1)=0
(x-5)(3x-3)=0
or, un produit est nul si au moins un des facteurs est nul
si x-5=0; x=5
si 3x-3=0; x=1
Donc S={1,5}

x²-1+(x-1)(x+5)=0
(x-1)(x+1)+(x-1)(x+5)=0
(x-1)((x+1)+(x+5))=0
(x-1)(2x+6)=0
or, un produit est nul si au moins un des facteurs est nul
si x-1=0; x=1
si 2x+6=0; x=-3
Donc S={-3,1}

3x²=x
3x²-x=0
x(3x-1)=0
or, un produit est nul si au moins un des facteurs est nul
x=0
si 3x-1=0; x=1/3
Donc S={0,1/3}

Bonne journée